Antenatal Magnesium Sulfate Benefits Female Preterm Infants but Results in Poor Male Outcomes - Ruth M. McLeod; Ted S. Rosenkrantz; R. Holly Fitch (Pharmaceuticals, 2024)
Magnesium sulfate (MagSul) is used clinically to prevent eclamptic seizures during pregnancy and as a tocolytic for preterm labor. More recently, it has been implicated as offering neural protection in utero for at-risk infants. However, evidence is mixed. Some studies found that MagSul reduced the incidence of cerebral palsy (CP) but did not improve other measures of neurologic function. Others did not find any improvement in outcomes. Inconsistencies in the literature may reflect the fact that sex effects are largely ignored, despite evidence that MagSul shows sex effects in animal models of neonatal brain injury. The current study used retrospective infant data to assess differences in developmental outcomes as a function of sex and MagSul treatment. We found that on 18-month neurodevelopmental cognitive and language measures, preterm males treated with MagSul (n = 209) had significantly worse scores than their untreated counterparts (n = 135; p < 0.05). Female preterm infants treated with MagSul (n = 220), on the other hand, showed a cognitive benefit relative to untreated females (n = 123; p < 0.05). No significant effects of MagSul were seen among females on language (p > 0.05). These results have tremendous implications for risk–benefit considerations in the ongoing use of MagSul and may explain why benefits have been hard to identify in clinical trials when sex is not considered.